Ijtihad Hakim dalam Sengketa Ekonomi Syariah: Penemuan Hukum Hakim Atas Teks Hukum Bersifat Implisit - Fithri Dzikrayah; Mustofa Hasan; Dudang Gojali (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The rapid development of Islamic economics in Indonesia presents complexities in dispute resolution in Religious Courts. Not all contemporary Islamic economic issues are explicitly regulated in legislation, requiring judges to perform ijtihad through legal discovery (rechtsvinding) of implicit legal texts. This research aims to analyze judges' ijtihad practices in resolving Islamic economic disputes when facing unclear or incomplete legal norms. The research method used is normative juridical with conceptual approaches, utilizing secondary data including legislation, court decisions, DSN-MUI fatwas, and legal literature. The results show that judges perform ijtihad through two main approaches: (1) interpretation of implicit legal texts in KHES and related regulations, extracting Islamic legal values from primary sources (Quran, Hadith) and secondary sources (qawaid fiqhiyyah, DSN-MUI fatwas); (2) legal construction through analogy and logical reasoning when legal vacuums occur. This judicial ijtihad practice demonstrates the dynamics of fiqh muamalah transformation into Indonesia's positive legal system. However, challenges exist including inconsistent decisions, regulatory limitations, and the need for harmonization of Islamic law within the national context. This research suggests the importance of strengthening Islamic economic judges' capacity and harmonization between Islamic law and national law.